The Cambridge Handbook of Meeting Science 2015
DOI: 10.1017/cbo9781107589735.015
|View full text |Cite
|
Sign up to set email alerts
|

Social Dynamics at Work

Abstract: Meetings offer an exciting gateway to dynamic social processes in organizations. During their meeting interactions, employees exchange information, build common ground, create new ideas, manage relationships, and make or break team climate. In this chapter, we highlight the potentials and possibilities for research on dynamic social processes during team meetings.Through the lens of a meetings researcher, we discuss how research questions and methodological issues in studying meeting interaction processes can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 76 publications
0
33
0
Order By: Relevance
“…To examine whether any observed transition probability differed from the unconditional probability for the respective event that followed, we used the z-statistic as a statistical check (Bakeman & Gottman, 1997). A z-value larger than 1.96 or smaller than −1.96 implies that a behavioral sequence occurred above chance in our data (for more details on lag sequential analysis and applications for analyzing team interactions, see Bakeman & Quera, 2011;LehmannWillenbrock et al, 2011LehmannWillenbrock et al, , 2013Meinecke & Lehmann-Willenbrock, 2015).…”
Section: Lag Sequential Analysismentioning
confidence: 95%
“…To examine whether any observed transition probability differed from the unconditional probability for the respective event that followed, we used the z-statistic as a statistical check (Bakeman & Gottman, 1997). A z-value larger than 1.96 or smaller than −1.96 implies that a behavioral sequence occurred above chance in our data (for more details on lag sequential analysis and applications for analyzing team interactions, see Bakeman & Quera, 2011;LehmannWillenbrock et al, 2011LehmannWillenbrock et al, , 2013Meinecke & Lehmann-Willenbrock, 2015).…”
Section: Lag Sequential Analysismentioning
confidence: 95%
“…Given our theoretical framework and particular study aim, we focused our analysis on negative socioemotional behaviors observed in the premeeting period of these groups. The categorization of dysfunctional socioemotional behaviors that we used in this study was developed in previous field research (Kauffeld & Lehmann-Willenbrock, 2012) and has been used extensively in recent team process research (e.g., Goh, Fisher, & Sommer, 2015;Lehmann-Willenbrock et al, 2013;Meinecke & Lehmann-Willenbrock, 2015). Negative socioemotional communication in meetings includes behaviors such as interruptions, criticizing others, and side conversations that exclude other meeting participants (e.g., when two attendees are whispering among each other).…”
Section: Coding Premeeting Interaction Behaviormentioning
confidence: 99%
“…Team meetings in particular have become an integral part of employees' work lives (e.g., Lehmann-Willenbrock, Allen, & Kauffeld, 2013). Team meetings are a key venue for observing team problem-solving processes (e.g., Kauffeld & Lehmann-Willenbrock, 2012), sensemaking activities (Baran, Shanock, Rogelberg, & Scott, 2012), and social dynamics in general (Meinecke & Lehmann-Willenbrock, 2015). Moreover, team meetings are communicatively created (Beck, 2008), deeming them an appropriate context for examining how team roles are constructed through team communication.…”
Section: A Communicative Approach To Team Role Creationmentioning
confidence: 99%